Orta Gelir Tuzağı Tehlikesi Ve Türkiye Ekonomisi Üzerine Bir Analiz - Çetinkaya, Şahin (İstanbul Kültür Üniversitesi / İktisadi ve İdari Bilimler Fakültesi / İktisat Bölümü, 2016)
Middle income trap is an indication of the emphasis strongly in today's economy. In this case can be regarded as a harbinger of a hidden recession. Turkey’s economy entered 2000 year with a $4000 per capita income. In 2014 this figure was $10515. However this figure has ranged from $10111 to $10955 since 2010. İn fact, this situation shows a middle income trap. In this context, examining the economic structure between the years 1960-2015, a middle-income trap macro economic analysis will be performed from danger. This study includes the 1960-2015 period. The indicators will compare between the studied years. per capita income and economic growth effects will be discussed. The relationship with economic growth of national income per capita will be discussed
Keywords: Orta Gelir Tuzağı; Ekonomik büyüme; Alt orta gelirli ülke; Üst orta gelirli ülke; Middle income trup; Economic growth; Lower middle income; upper middle income